Predicting asthma morbidity in children using proposed markers of Th2‐type inflammation. Issue 8 (28th September 2015) - Konradsen, Jon R.; Skantz, Elizabeth; Nordlund, Björn; Lidegran, Marika; James, Anna; Ono, Junya; Ohta, Shoichiro; Izuhara, Kenji; Dahlén, Sven‐Erik; Alving, Kjell; Hedlin, Gunilla
Abstract: Background: Assessment of inflammation is becoming a common practice in the clinical work‐up of children with persistent asthma. Biomarkers of Th2‐mediated inflammation include blood eosinophils (B‐Eos), exhaled nitric oxide (FeNO), total serum IgE (S‐IgE), and serum periostin. The aim of this study was to investigate the associations between asthma morbidity and increased levels of these biomarkers in pediatric asthma. Methods: School‐age children (n = 96) with various manifestations of persistent asthma were included in this nationwide Swedish study. The protocol included the asthma control test, Juniper's quality of life questionnaire (QoL), assessment of pulmonary function, bronchial hyperresponsiveness, height‐adjusted FeNO, blood sampling for S‐IgE, B‐Eos, and periostin, and high‐resolution computed tomography (HRCT) of the lungs. Results: Children with both high levels of height‐adjusted FeNO and B‐Eos were younger (p = 0.001), had more often severe asthma (p = 0.015), were more allergic (p < 0.001), had a reduced asthma control (p = 0.035), reduced QoL (p = 0.035), more exacerbations (p = 0.004), reduced FEV1/FVC (p = 0.001), and increased bronchial hyperresponsiveness (p < 0.001) as well as greater bronchial wall thickening on HRCT (p = 0.022) compared to those with low levels of both biomarkers. Grouping children according to high and low serum periostin levels did not relate to differences in clinical characteristics and biomarkers. Conclusions: Assessment of both local and systemic Th2‐mediated inflammation by the analysis of easily attainable biomarkers such as exhaled NO and blood eosinophils has a high predictive value for the identification of children with the highest asthma morbidity. Adjusting FeNO values according to the individual child's height increases the clinical usefulness of this biomarker. Abstract :